2019
DOI: 10.1186/s12575-019-0105-1
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Quantitative Real-Time PCR for the Detection of Residual CHO Host Cell DNA and Optimization of Sample Pretreatment Method in Biopharmaceutical Products

Abstract: Background The presence of residual DNA carried by biological products in the body may lead to an increased oncogenicity, infectivity, and immunomodulatory risk. Therefore, current agencies including WHO, EU, and the FDA limited the accepted amounts of residual DNA (less than 10 ng or 100 pg/dose). Among the methods of detecting residual DNA, qPCR is considered to be the most practical for residual DNA quantitation due to its sensitivity, accuracy, precision, and time-saving. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Thus, the efficiency showed adequate values, which proves a good performance of the primer–probe sets 41 . Moreover, the linearity (R 2 ) of the standard curves ranging from 0.939 to 0.999 meet the accepted criterion of R 2 at around 0.98 42 and, consequently, showed a linear correspondence among log 10 gene copy number and their respective Cq values.…”
Section: Resultsmentioning
confidence: 66%
“…Thus, the efficiency showed adequate values, which proves a good performance of the primer–probe sets 41 . Moreover, the linearity (R 2 ) of the standard curves ranging from 0.939 to 0.999 meet the accepted criterion of R 2 at around 0.98 42 and, consequently, showed a linear correspondence among log 10 gene copy number and their respective Cq values.…”
Section: Resultsmentioning
confidence: 66%
“…Martins et al (2019) revealed maximum CV values of 1.39% and 3.67% for intra-and inter-assay repeatability, respectively. Additionally, Zheng et al (2019) repeatability results showed lower variation with maximum CV values of 0.45% and 1.31% for intra-and inter-assay repeatability, respectively. In contrast, in Friedman et al (2014) repeatability results were inadequate with CV values reaching 27%.…”
Section: Precision: Intra-assay and Inter-assay Repeatabilitymentioning
confidence: 91%
“…[102] chinese hamster Alu primers: 5 -agagatggctcgaggttaag-3 and 5 -tctgcacaccagaagagg-3 ; probe: R-5 -agcaccaactgctcttccagagg-3 -Q. [103] Syrian hamster 5S rRNA primers: 5 -cgcagcagcaggctct-3 and 5 -accctgcttagcttccgaga-3 ; probe: R-5 -ccgccgtcgtctacggccatacc-3 -Q. [94] rcAAV ITR-Rep recombinants primers: 5 -actccatcactaggggttct-3 and 5 -gctggggaccttaatcacaa-3 .…”
Section: Dna Impurity Target Sequences Referencesmentioning
confidence: 99%